Exploring the utility of urine steroid metabolite ratios in evaluating over 500 suspected cases of disorders of sex hormone synthesis. (24th May 2012) - Rodie, M; Rankin, K; Howarth, R; Liu, N; Donaldson, M; Shaikh, MG; Shapiro, D; Ahmed, SF
Abstract : Background: Calculation of a urinary steroid metabolite ratio (uSMR) may be a useful method of improving diagnostic yield when investigating disorders of steroid hormone synthesis. Objective and hypothesis: To determine the range of uSMR and the relationship between the uSMR and the diagnostic outcome in abnormal cases. Population/methods: Ten ratios were calculated on steroid metabolite data previously analysed by GC-MS in urine samples from 544 patients under 18 years collected between 2008-2010. Results: Out of 544 patients, 337 (62%) were female, 189 (35%) were male and in 18 (3%) the sex was not documented. Indications for performing the test included adrenarche or XX virlisation in 239 (44%) cases and XY DSD in 68 (13%) cases. Median age at test was 7.4 years (r, 1 day, 18 years) with 11%, 4%, 3%, 3%, 7%, 16%, 40%, 6%, 6% and 4% of tests performed in the following age bands, <1 week, 2 weeks-2 months, 3-5 months, 6-11 months, 1-3 years, 4-6 years, 7-9 years, 10-12 years, 13-15 years and 16-18 years, respectively. In 97 (18%) patients, one or more uSMR was above the 97th centile. The proportion of high uSMR according to the above age bands, was 0%, 0%, 2%, 11%, 33%, 6%, 16%, 8%, 7% and 17%, respectively. Out of these 97, case notes were reviewed in 28/32 cases from Glasgow. 5 (18%) patients had a confirmed steroid disorder (true positives), 8 (29%) had uSMR performed due to concerns such as ambiguous genitalia, premature adrenarche or cryptorchidism (possible true positives) and in the remaining 15 cases the tests were performed for a variety of reasons which resolved at a later stage (false positives). Conclusions: Applying simplified diagnostic ratios to urinary steroid profile data results in a yield of about 20% cases being abnormal. There is a need to improve the sensitivity and specificity of the uSMR and the reference ranges for these ratios.